Macular injury resulting from a high-powered tank laser telemetry device. Issue 4 (18th December 2014) - Durukan, Ali Hakan; Gokce, G; Guven, S; Koylu, T; Erdurman, F C
Abstract : A high-powered laser is an essential part of a modern military rangefinder; however, this paper presents three cases with macular injury resulting from a high-powered tank laser telemetry device. All injuries occurred when another user deliberately pointed the telemetry target unit at the patient's eyes. The devastating effect of this high-powered laser resulted in a permanent foveal scar in the second patient and a macular hole formation in the third patient. This report emphasises that education plays a primary role in preventing accidental laser injuries. Using general guidelines and safety regulations will prevent accidental macular injuries.